PENERAPAN PROJECT-BASED LEARNING DIPADU GROUP INVESTIGATION UNTUK MENINGKATKAN MOTIVASI, DAN HASIL BELAJAR MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS MUHAMMADIYAH MALANG - Nasrul hakim (BIODIK, 2015)
This research to increase motivation and learning outcomes of students  Biology Education semester VB at the University of Muhammadiyah Malang Environmental Sciences courses through the implementation of Project Based Learning combined-based Lesson Study Group Investigation. This research is Classroom Action Research. The research approach used is qualitative approach, consisted of two cycles, each cycle consisting of the stages of the action plan, action, observation, and reflection. The approach taken is a qualitative descriptive approach.               The results showed that the application of PjBL combined GI can increase student motivation to learn. Attention components increased by 3.6%, Relevance components increased by 6.3%, Convidence component increased by 9.1%, while the component Satisfaction increased by 2%. Student learning outcomes also increased. Students who got an A increased from 29.3% in Cycle I to 48.8% in Cycle II. Students who receive a grade of B + indicates the number remains, which amounted to 46.3%. In connection with that then, the percentage of students who scored B fell from 24.4% in Cycle I to 4.9% in Cycle II. Based on the results concluded that the application of learning models  PjBL combined GI can increase student motivation and learning outcomes. It is therefore advisable to adopt a Biology professor model PjBL combined GI by Lesson Study because it has been shown to increase motivation and cognitive learning outcomes of students. Keywords: Project Based Learning, Group Investigation, Lesson Study, motivation, and Learning Outcome.